Syngas Production from Electrochemical CO2 Reduction on Copper Oxide Electrodes in Aqueous Solution - Xi Yao; Dr. Yafei Guo; Bingqian Liu; Puyao Wang; Dr. Jian Sun; Dr. Weiling Li; Dr. Chuanwen Zhao (ChemElectroChem)
Abstract Electrochemical CO2 reduction to value‐added chemicals and fuels using renewable energy represents a promising strategy for reducing CO2 emissions and achieving effective energy storage. In this work, nano‐sized CuO catalysts were prepared by using the homogeneous precipitation method for electrochemical CO2 reduction to CO. The CO2 reduction studies combined with the characterization results show that structure‐activity relationships of the CuO catalysts depend on the calcination temperature. The as‐synthesized CuO catalysts calcined at different temperatures are capable of reducing CO2 to generate syngas with tunable CO/H2 ratios of 1 : 2 to 2 : 1. The desired CuO‐400 catalyst exhibits good morphology, small particle size, and enriched oxygen‐vacancy defects and, therefore, shows good performance for electrochemical CO2 reduction to CO. Under the given potential of −0.93 V vs. RHE, CuO‐400 exhibits good reduction activity and selectivity with a great electrochemically active surface area normalized CO partial current density of 1.44 mA/cm2 and a high CO faradaic efficiency of 48.2 %. The deactivation of CuO‐400 in the long‐term test is associated with the increase in particle size, the reduction of CuO to Cu2O and metallic Cu, and the coverage of surface active sites by the formed carbonate species. Our findings indicate that CuO catalysts with tunable physicochemical properties are promising candidates for electrochemical CO2 reduction to produce syngas.